Clustering and multicasting scheme for fog computing based vehicular ad hoc network - Pal Singh, Tejinder; Nitika Kapoor, Er. (International Journal of Engineering and Technology, 2018)
The vehicular adhoc network is the data oriented in network in which information should be passed with least delay. The vehicle adhoc network is the decentralized type of network in which vehicles to vehicle and vehicle to road side communication is possible. The Fog computing is the advance computing scheme to store small amount of data. The routing is the major issue of vehicular adhoc network due to high mobility of the vehicle nodes. In this research work, multicasting based routing scheme is proposed for path establishment from source to destination. In the proposed scheme root vehicles are selected for path establishment from source to destination. When the data will be received on the road side unit then k-mean clustering will be applied which divide data into clusters which define that either it can be saved on cloud or on fog server based on quantity of data. The performance of proposed scheme is testing in NS2 and proposed scheme performs well in terms of PDR and route lifetimeÂ Â